The Paradigm of Islamic Religious Education Evaluation in Realizing Inclusive Multicultural Education - Mohammad Ali Yusron; Mujamil Mujamil; Kojin Kojin; Hosaini Hosaini (Education and Sociedad Journal, 2025)
This study aims to analyze the paradigm of Islamic Religious Education (IRE) evaluation in promoting inclusive multicultural education within diverse educational settings. The research is based on the premise that conventional evaluation practices in Islamic Religious Education tend to focus predominantly on cognitive achievement, while aspects of tolerance, inclusivity, respect for diversity, and intercultural competence receive limited attention. This study employed a qualitative library research method by examining relevant literature, including books, scientific journal articles, policy documents, and contemporary studies on Islamic education, educational evaluation, and multicultural education. The findings reveal that the evaluation paradigm of Islamic Religious Education should be transformed from a purely knowledge-oriented assessment toward a holistic and value-based evaluation framework encompassing cognitive, affective, and behavioral dimensions. Inclusive multicultural education can be strengthened through evaluation instruments that assess students’ attitudes toward diversity, religious moderation, social justice, mutual respect, and peaceful coexistence. Furthermore, the integration of multicultural values into evaluation practices encourages the development of inclusive character and democratic citizenship among learners. The study concludes that a multicultural-oriented evaluation paradigm in Islamic Religious Education serves as a strategic instrument for fostering inclusive, tolerant, and harmonious educational environments. The implications of this study highlight the need for educational institutions, policymakers, and teachers to redesign evaluation systems that support the cultivation of multicultural competencies and strengthen social cohesion in increasingly pluralistic societies.